Dampak alokasi belanja langsung terhadap ketimpangan ekonomi wilayah (Studi kasus Provinsi Sumatera Utara, Provinsi Jambi, dan Provinsi Bengkulu) - Alberd Kurniawan Gulo; Zamzami Zamzami; Adi Bhakti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This study aims to analyze: 1) the development of direct shopping; 2) developments in economic inequality; 3) the effect of direct spending on economic inequality. This study uses time series data from 2005-2014 with a case study of North Sumatra Province, Jambi Province, and Bengkulu Province. The study found that 1) North Sumatra Province had the highest direct expenditure development from Jambi Province and Bengkulu Province; 2) North Sumatra Province which has the highest direct expenditure also has higher inequality from Jambi Province and Bengkulu Province but still falls into low inequality; 3) Direct expenditure has a significant effect on economic inequality in North Sumatra and Bengkulu Provinces, while in Jambi Province direct expenditure does not significantly influence economic inequality.